Liver in Felty's Syndrome. Issue 5689 (17th January 1970) - Blendis, L. M.; Ansell, I. D.; Jones, K. Lloyd; Hamilton, Eric; Williams, Roger
Abstract : Liver function and histology, together with the haematological changes, were investigated in 12 patients with Felty's syndrome. Six of them were anaemic. The red cell mass was either normal or increased, and the anaemia was due to a considerable increase in the plasma volume. Two patients had increased haemolysis associated with red cell sequestration by the enlarged spleens. In eight patients liver function tests were abnormal, while in five the liver histology showed lymphocytic infiltration of the sinusoids and portal tracts together with portal tract fibrosis. One of these was later found to have a macronodular cirrhosis. In another there were apparent nodules without a true cirrhosis, and this appearance was also seen in two other patients with Felty's syndrome in whom histology was available. An increased blood flow through the spleen was found in the two patients examined.